Analysis to: party-platforms' answers to the Coptic question within the post-revolution transition for a better future - Labib, Mariam Makram (AUC Knowledge Fountain, 2013)
The current study aims at analyzing the issue of Copts Rights in Egypt since the celebration of the January 25 Revolution's Anniversary till the 15th of March 2012. It looks into the initiatives towards solving the Muslim-Christian tensions in Egypt that were made in the parties' programs within the elections campaigns to win in 2012 Parliamentary elections and to fore-market their preferable Presidential Candidates in the first post-revolution presidential elections. This is a timely topic that helps in predicting the future of Egyptians' national cohesion per regards to the status of Copts, especially after the rise of Islamic-oriented parties and their active participation in politics. Content analysis methodology is used to scrutinize one hundred fifty-five news articles from the two major online news sites Alwafd.org and Ikhwanonline.com that were key-players during the set timeframe. The study finds that among all the reforms, projects and promises that were proposed by the parliamentary and presidential candidates within their campaigns, the Coptic Question has been profusely addressed and was excessively discussed in comparison with all other covered topics and political aspects that were covered. Rhetorical tenor of mentioning Copts varies; despite this, a collaborative compulsion to the necessity of solving sectarian tensions in Egypt is present.